Marketing Strategy in Developing Beauty and Fashion Products Through Social Media in the New Normal Era (Case Study of Bengkulu Rj Decline Gallery) - Rian Nespia; Taufik Bustami (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
manufacturing that sells beauty and fashion products, including make up, lipstick, shirts, pants and accessories. In his business practices, entrepreneurs experience problems in the field of sales, namely the existence of various competitors who have already existed and already have a branding name that is well known in the wider community. To develop its business, the RJ Bengkulu City Decline Gallery uses Strengths, Weakness, Opportunities, Threats (SWOT) analysis, where this analysis can maximize existing strengths and opportunities and minimize weaknesses and threats that a business has and also use a marketing mix strategy or more known as the 4P, namely product (product), price (price), place (place or distribution channel), and promotion (promotion). Research Methods : This type of research is descriptive with a qualitative approach to analyze the situation objectively regarding the strategy undertaken by Gallery RJ Decline in Bengkulu City in developing its products. The informants of this research are the business owners of the Bengkulu City RJ Gallery and their employees, accompanied by direct observations of the spaciousness. Research Results : Based on the results of the SWOT analysis of Gallery RJ's marketing strategy, the decline in the City of Bengkulu, which can be seen in table 4.2 above, the internal conditions have a total strength with a total score of 12 which shows strengths are greater than weaknesses with a total score of 0. While the external has total opportunities with a total score of 7 where the opportunity is greater than the threat which has a total score of 4. This indicates that Gallery RJ Decline in Bengkulu City has strong internal conditions and external opportunities. Conclusion : The marketing strategy of RJ Gallery, Bengkulu City, in developing its business already has good internal conditions and strong external opportunities.